2006
DOI: 10.4269/ajtmh.2006.75.1188
|View full text |Cite
|
Sign up to set email alerts
|

Deaths Caused by Malaria in Switzerland 1988–2002

Abstract: Despite sophisticated intensive medicine, between one and three malaria-associated deaths occur annually in Switzerland. In this retrospective study, 33 deaths (25 men and 8 women) caused by falciparum malaria reported in Switzerland from 1988 to 2002 were analyzed. The case fatality ratio (CFR) for the falciparum infections for the 15-year period was 1.2%, with a peak of 2.2% in 1991. Sub-Saharan Africa was the source of all the imported fatal infections. Non-immune Europeans had a significantly higher case f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 11 publications
1
33
0
1
Order By: Relevance
“…This findings reflect the higher risk of malaria acquisition in this area compared with other areas, 2,3,6 and strengthens current recommendations about chemoprophylaxis. All patients were from areas not endemic for malaria and were considered non-immune.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This findings reflect the higher risk of malaria acquisition in this area compared with other areas, 2,3,6 and strengthens current recommendations about chemoprophylaxis. All patients were from areas not endemic for malaria and were considered non-immune.…”
Section: Discussionmentioning
confidence: 56%
“…This finding might be related to their acquired semi-immunity (after repeated exposures to malaria), which has been associated with a lower risk of complications and death. 2,3,12 This protection is generally thought to disappear in a few years after non-exposure, but conflicting findings about this issue have been published, 13,14 and it is still a matter of debate that warrants further investigations. Previous studies have suggested that age is a risk factor for severe P. falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About two-thirds of malaria cases in this analysis occurred in men, a phenomenon noted previously. 11,12 Higher rates of malaria and deaths due to malaria among male travellers may reflect both biological (e.g., attractiveness to vectors) and behavioural (e.g., adherence to chemoprophylaxis) risk factors, 11,[13][14][15][16][17] although their continued over representation in epidemiologic analyses speaks to the need for better, targeted prevention initiatives.…”
Section: Discussionmentioning
confidence: 99%